GAYA KEPEMIMPINAN TRANSFORMASIONAL, MOTIVASI KERJA, DAN DISIPLIN KERJA SEBAGAI PREDIKTOR KINERJA KARYAWAN - Permana Putra, I Dewa Made Arik; Sriathi, Anak Agung Ayu (E-Jurnal Manajemen, 2014)
This study is aim ed to determine the effect of transformational leadership style, motivation, and work discipline on employee performance. Location the study was conducted at the Pusat Koperasi Unit Desa Bali Dwipa Provinsi Bali , 69 samples taken by census method. Data collection using the survey data analysis questionnaire.Teknik technique used is multiple linear regression analysis. The results showed that transformational leadership style, motivation, and work discipline and a significant positive effect on employee performance. This suggests that the transformational leadership style, motivation, and discipline work can improve employee performance
Keywords: employee performance, transformational leadership style, motivation, and work discipline.